2011
DOI: 10.1021/jp206160q
|View full text |Cite
|
Sign up to set email alerts
|

Phenoxy Radical (C6H5O) Formation under Single Collision Conditions from Reaction of the Phenyl Radical (C6H5, X2A1) with Molecular Oxygen (O2, X3Σg): The Final Chapter?

Abstract: The combustion relevant elementary reaction of photolytically generated phenyl radicals (C(6)H(5), X(2)A(1)) with molecular oxygen to form the phenoxy radical (C(6)H(5)O) plus a ground state oxygen atom was investigated under single collision conditions at a collision energy of 21.2 ± 0.9 kJ mol(-1). The reaction was found to proceed indirectly via the involvement of a long-lived phenylperoxy radical (C(6)H(5)O(2)) intermediate that decomposed via a rather loose exit transition state. In comparison with crosse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 29 publications
2
24
1
Order By: Relevance
“…A detailed theoretical analysis of the mechanism and kinetics of their reactions with O 2 is sought to better understand how larger PAH radicals are oxidized in flames. The mechanism and kinetics of the C 6 H 5 +O 2 reaction has received considerable attention by the combustion community in the last two decades [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed theoretical analysis of the mechanism and kinetics of their reactions with O 2 is sought to better understand how larger PAH radicals are oxidized in flames. The mechanism and kinetics of the C 6 H 5 +O 2 reaction has received considerable attention by the combustion community in the last two decades [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the minor reaction channels producing o-and p-benzoquinone, o/p-C 6 H 4 O 2 , plus H atoms were also suggested [7]. However, the only products observed in the recent crossed molecular beam experiments at collision energies of 5-26 kcal mol -1 [15][16][17], which correspond to high combustion temperatures and beyond, were C 6 H 5 O+O.…”
Section: Introductionmentioning
confidence: 99%
“…These studies concluded that o-benzyne was the most likely C 6 as well as several further experimental and computational studies by Kaiser and co-workers. 12,[47][48][49] In work from our laboratory, Negru et al 50 investigated the photodissociation of the phenyl radical at 248 and 193 nm via photofragment translational spectroscopy. The radicals were produced by flash pyrolysis 51 of nitrosobenzene (C 6 H 5 NO).…”
Section: Introductionmentioning
confidence: 99%
“…The reactions of phenyl radicals are gaining interest among the study of the carbonaceous soot particles formation mechanism and their precursors, such as polycyclic aromatic hydrocarbons due to their importance in combustion, atmospheric, interstellar, and graphene chemistry . The diazonium salt‐derived phenyl (aryl) radicals known as effective grafting agents for metal and organic surfaces provide an additional reason for the extensive study of these species .…”
Section: Introductionmentioning
confidence: 99%